Integrated systems, design and technology 2010 : knowledge transfer in new technologies - Fathi, Madjid (Springer Science + Business Media, 2011)
Knowledge creation and technological experiences resulting from modern production life cycles are definitely the most economical and important intellectual capitals in manufacturing endeavors. Integration of components, design of structures and managing knowledge inherent in engineering is a complex endeavor. This book deals with this topic